Validation of pre-compensation under point-ahead-angle in a 1 km free-space propagation experiment - Brady, Aoife; Roessler, Conrad; Leonhard, Nina; Gier, Marlies; Boettner, Paul; Eberhardt, Ramona; Tuennermann, Andreas; Reinlein, Claudia (Optics Express, 2019)
Adaptive optical pre-compensation is seen as crucial for free-space laser communication in order to overcome the influence of atmospheric turbulence, particularly with respect to Earth-to-GEO feederlinks. This paper presents an experimental investigation into adaptive optical pre-compensation under large point-ahead-angles. We detail the design and realization of a free-space laser communication experiment over a 1.0 km horizontal path using a divergent beacon beam and a focussed signal beam, propagating in opposite directions. We describe the design and development of our experimental setup and measurement campaign using real turbulence. The median isoplanatic angle was calculated to be 0.16 mrad, while an increase in the received optical power through pre-compensation could be demonstrated for point-ahead-angles in the range of 0.13 mrad to 0.27 mrad.
CRIS-Team Scopus Importer:2023-04-20